Pengaruh Penggunaan Media Gambar terhadap Keterampilan Menulis Teks Iklan pada Siswa Kelas VIII SMP 27 Makassar - Sitra, Sitra; Azis, Abdul; Usman, Usman (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to describe the influence of using image media on the advertisement text writing skills of eighth-grade students at SMP Negeri 27 Makassar. This research is a quasi-experimental study. The independent variable is image media, while the dependent variable is advertisement text writing skills. The population includes all eighth-grade students at SMP Negeri 27 Makassar, consisting of 9 classes, with class VIII-5 as the sample (20 students). Data were collected through a pretest and posttest of advertisement text writing. The data were analyzed using statistical analysis with IBM SPSS Version 30. The pretest results showed an average score of 61.10, which increased to 63.90 in the posttest. The t-test resulted in a t-value of 8.559, which is greater than the t-table value of 1.729, indicating that the use of image media has a significant effect on improving students' skills in writing advertisement texts. These findings suggest that image media can be an effective alternative in teaching advertisement writing at the junior high school level.